2016
DOI: 10.5774/45-0-198
|View full text |Cite
|
Sign up to set email alerts
|

Levelling-out and register variation in the translations of experienced and inexperienced translators: a corpus-based study

Abstract: Explicitation, simplification, normalisation and levelling-out, the four features of translation proposed by Baker (1996), have attracted considerable attention in translation studies. Although the first three have been studied extensively, levelling-out has been the subject of less empirical investigation. Furthermore, there are no studies to date that have investigated the extent to which levelling-out occurs in translations by experienced translators and inexperienced translators. In this study, levelling-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Their results provided limited evidence for universal character of translationese, rather each register demonstrated its own pattern of analysed features. In a later research using the same features, the levelling-out of registers, conceptualised as the assumed reduced register variability in favour of a neutral middle register, was not supported either (Redelinghuys 2016).…”
Section: Translationese and Registermentioning
confidence: 79%
See 1 more Smart Citation
“…Their results provided limited evidence for universal character of translationese, rather each register demonstrated its own pattern of analysed features. In a later research using the same features, the levelling-out of registers, conceptualised as the assumed reduced register variability in favour of a neutral middle register, was not supported either (Redelinghuys 2016).…”
Section: Translationese and Registermentioning
confidence: 79%
“…For example, Arase and Zhou (2013) used the frequency of discontinuous structures to capture 'phrase salad' in MT. Redelinghuys (2016) calculated readability scores, while Volansky, Ordan, and Wintner (2015) operationalised the normalisation hypothesis with average PMI of all bigrams and ratio of repeated content words along with other features. Lapshinova-Koltunski (2017) suggested a feature set, which included features like frequency of evaluative patterns and degree of nominalisation (ratio of nominal and verbal PoS).…”
Section: Feature Setsmentioning
confidence: 99%
“…Kruger (2012) investigated the relationship between register and the features of translated language and found that the interference of the translation process will not evidently lead to a "levelling out" of registers. Redelinghuys (2016) researched levelling-out and register variation in the translations of experienced and inexperienced translators and found that little evidence could be found for levelling-out as register variation is evident in the translation corpora. Hu (2014) studied the debatable hypotheses of "Translation Universals" with a multi-feature statistical model for linguistic variation analysis.…”
Section: Register Variation Studies and Multidimensional Analysismentioning
confidence: 99%
“…Levelling out has not been frequently empirically investigated as a translation universal. In order to test if translated texts tend to show more uniform patterns compared to original texts (levelling out as a S-Universal), two indicators have been considered: lexical variety in terms of STTR and average sentence length, which were also considered as indicators of simplification, and have been tested in other corpus-based studies (see Corpas Pastor et al 2008, Redelinghuys 2016.…”
Section: Levelling Outmentioning
confidence: 99%